Association Between the Route of Administration and Formulation of Estrogen Therapy and Hypertension Risk in Postmenopausal Women: A Prospective Population-Based Study - Kalenga, Cindy Z; Metcalfe, Amy; Robert, Magali; Nerenberg, Kara A; MacRae, Jennifer M; Ahmed, Sofia B (Hypertension (Dallas, Tex. 1979), 2023)
Hypertension is the leading global cause of cardiovascular disease and premature mortality in women. The effects of postmenopausal hormone therapy (HT) on blood pressure are uncertain but may be related to route of estrogen administration and formulation of estrogen. We sought to determine the association between route of administration and formulation of estrogen HT and hypertension risk in postmenopausal women. Population-based cohort study with women aged ≥45 years who filled ≥2 consecutive prescriptions for estrogen-only HT, identified from linked provincial health administrative data from Alberta, Canada, between 2008 and 2019. The primary outcome, incident hypertension, was identified using standardized , . Cox proportional hazard models were used to calculate hazard ratios (HRs) for hypertension in women using oral HT compared with nonoral HT (transdermal, vaginal, or intramuscular). In total, 112 240 women used an estrogen-only form of HT. Oral estrogen was associated with a higher risk of hypertension compared with both transdermal (HR, 1.14 [95% CI, 1.08-1.20]) and vaginal (HR, 1.19 [95% CI, 1.13-1.25]) estrogens. Conjugated equine estrogen was associated with an increased risk of hypertension compared with estradiol (HR, 1.08 [95% CI, 1.04-1.14]) but not estrone (HR, 1.00 [95% CI, 0.93-1.10]). Duration of estrogen exposure and cumulative dose of estrogen was positively associated with risk of hypertension. Oral estrogen-only HT use was associated with an increased risk of hypertension in women. In women using estrogen-only HT, nonoral estradiol at the lowest dose and for the shortest time-period is associated with the lowest risk of hypertension.